The making and development of Baxter the Empowered Chatbot impered with Machine Intelligence - Srimathi Jagadesan; P Girish; Anugraha Ramesh kurane (Trends in Computer Science and Information Technology - Peertechz Publications, 2021)
Artificial Intelligence and machine learning in machines is a very challenging discussion. It involves the creation of machines which can stimulate intelligence and adapt to the needs of the human kind. This paper discusses some of the current trends and practices in A.I. and subsequently offers alternative theory for improvement of some of today's prominent postulates. For this, focus on the structuring and functioning of simple - chatbots( or chatter bots) is made. The paper shows how the current approach towards A.I. and M.L. is not adequate and offers a new path that discusses machine learning, machine intelligence, python programming throwing light to the future of Intelligent systems.